Inspired by Nature: Antioxidants and Nanotechnology - Claus Jacob (MDPI AG, 2018)
Since the advent of modern nanotechnology a couple of decades ago, the field of “nano-bio-med” has attracted particular interest, culminating in an almost meteoric rise of common, feasible, more speculative, and, on occasion, outrightly exotic applications of nanomaterials. [...]